2014
DOI: 10.5897/ajb2013.13347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in different genotypes of Gerbera jamesonii Bolus using random amplified polymorphic DNA (RAPD) markers

Abstract: Genetic diversity within Gerbera jamesonii Bolus is the key to genetic improvement of this important ornamental species. In the present study, genetic diversity of 12 accessions of gerbera was assessed through random amplified polymorphic DNA (RAPD) markers. A total of 40 RAPD primers belonging to OPD, OPE, OPF and OPG series of universal primers set were used out of which, only 10 primers produced clear, reproducible and scorable bands. Ten (10) decamer RAPD primers produced a total of 49 scorable bands from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…3). The estimates of MI were found to be the highest for primer URP9R (4.39) and the lowest with the primer Our study using three marker systems suggested the presence of a significant polymorphism and revealed high level of variability in surveyed gerbera genotypes which agrees with those reported by Prajapati (2014). This is the first research to utilize RAPD, ISSR and DAMD molecular markers to examine the extent of genetic variability among germplasm of gerbera.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…3). The estimates of MI were found to be the highest for primer URP9R (4.39) and the lowest with the primer Our study using three marker systems suggested the presence of a significant polymorphism and revealed high level of variability in surveyed gerbera genotypes which agrees with those reported by Prajapati (2014). This is the first research to utilize RAPD, ISSR and DAMD molecular markers to examine the extent of genetic variability among germplasm of gerbera.…”
Section: Resultssupporting
confidence: 84%
“…This is not surprising as these markers are known to target different genomic fractions involving repeat and/or unique sequences, which may have been differentially evolved or preserved in due course of natural or human selection. These techniques were more informative and effective than the previously used molecular methods to study variation in gerbera, such as SSR (Hajibarat et al, 2014), and RAPD markers (Feghhi et al, 2014, Prajapati et al, 2014, Saidi et al, 2018. Discordance between dendograms obtained by ISSR and DAMD with RAPD could be explained by the different nature of each technique, region coverage of genome by each marker, level of polymorphism and the number of loci.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular marker-assisted selection (MAS) can accelerate directional breeding by developing molecular markers that are linked to specific traits [ 15 , 16 ]. Previous studies have used RAPD [ 17 ], DAMD [ 18 ], ISSR [ 18 ], and SSR [ 19 , 20 , 21 ] markers to evaluate the genetic diversity of gerbera. However, few studies have focused on molecular markers related to important ornamental traits of gerbera.…”
Section: Introductionmentioning
confidence: 99%